Carbetocin Versus Oxytocin Following Vaginal and Cesarean Delivery: A Before-After Study. Issue 4 (21st December 2022) - Tareef, A.; Downey, K.; Ma, B.; Whittle, W.; Carvalho, J.
Abstract : ( Can J Anaesth . 2022;69:97–105) Postpartum hemorrhage increases mortality, morbidity, potential blood transfusion, and length of hospital stay. Usually oxytocin, an effective agent with a short half-life and various possible side effects, is most used to treat postpartum hemorrhage. Carbetocin, though an unpopular method of treatment, has a longer half-life. Because of the shortage of oxytocin in Canada between the months of October and November in 2019, all stakeholders began to use carbetocin. This study researched the difference between carbetocin and oxytocin, especially regarding additional uterotonic medication administration, incidence of postpartum hemorrhage, and blood transfusion rates in a pragmatic before-after study.